Pertanggungjawaban Pidana Korporasi Marketplace Online pada Tindak Pidana Narkotika - Frans, Mardian Putra; -, M.Haryanto -; Dayanti, Karisma Christiyana Putri; Oktaviani, Ismi (RIO LAW JURNAL, 2024)
Marketplace's criminal liability as a corporation is legal responsibility for criminal acts committed by the corporation, whether the error is intentional or negligent. The civil relationship between the marketplace corporation and the shop as a Marketplace user means that the marketplace should be responsible for criminal acts committed by the shop, this can be seen by providing space by the Corporation in the online marketplace for shops to sell illegal goods such as narcotics in certain types of drugs, but in practice the Tokopedia online Marketplace Platform himself was not punished, In criminal law doctrine, corporations can be punished because online marketplace corporations are legal subjects that can commit criminal acts or criminal acts so that corporations should be held responsible if the marketplace is deemed to be involved in a criminal act by allowing shops in their marketplace to sell illegal goods such as narcotics, plus the corporation makes a profit. of these illegal goods.